Analisa Kapasitas Drainase Untuk Menanggulangi Banjir Pada Perumahan Kembar Lestari 1 Jambi - Indra Nopriansyah; Azwarman Azwarman; Emelda Raudhati (Jurnal Talenta Sipil, 2023)
In the city of Jambi, there are still various places that experience puddles or floods during high rainfall which results in drainage channels being unable to accommodate excess water. Drainage is very important to cope with flooding, one of which is in residential areas, especially in the Kembar Lestari 1 Jambi Housing area, Kenali Besar Village, Jambi City. Thus, this study aims to re-analyze the condition of the drainage channel at the Jambi City Kembar Lestari 1 Housing and find out the existing condition of the drainage channel at the 1 Jambi Sustainable Twin Housing and redesign the optimal drainage channel capacity so that later the Kenali Besar River channel can function optimally to reduce flooding that causes flooding. occurred in the Kembar Lestari 1 Housing area, Kenali Besar Village, Jambi City, so that a good and quality river was created while still taking into account the safety and comfort factors for the surrounding community. In this study, the data used is secondary data in the form of daily rainfall for 10 years and cross-sectional dimension data of the drainage channel of the Kembar Lestari 1 Housing Village, Kenali Besar. The results of the calculation of the planned rainfall with a return period of 10 years is 75.795 mm⁄hour, while the planned discharge using the Rational method is obtained a peak discharge value of 9.399 m^3⁄seconds, the steps are followed by using HEC-RAS 5.0.7 software to determine the capacity of the drainage channel by using plan debit.